RAGE拮抗薬azeliragonはヒト前立腺がん由来LNCaP細胞の生存・増殖を抑制する：影響をうける細胞シグナルの解析 - 浅野, 絵莉茄; 西川, 裕之; 川畑, 篤史; 脇谷, 航平; 芝野, 奈帆; 岡田, 卓哉; 関口, 富美子; 豊岡, 尚樹; 安達, 義史 (日本薬理学会年会要旨集, 2022)
Advanced glycation end products (AGEs), β-amyloid and high mobility group box 1 (HMGB1), a damage-associated molecular pattern (DAMP) protein, activate the receptor for AGE (RAGE), which is involved in the pathogenesis of various diseases including diabetic complications, Alzheimer's disease, and pathological pain. Clinical trials to evaluate the efficacy of azeliragon, a RAGE antagonist, in Alzheimer's disease patients are still ongoing. Given evidence that knockdown of RAGE by RNAi inhibits prostate tumor growth, we tested whether azeliragon could reduce viability of human prostate cancer-derived LNCaP cells. We confirmed that azeliragon at 1-10 µM blocked AGE-RAGE binding, and that systemic administration of azeliragon at 5-30 mg/kg significantly reduced allodynia following intraplantar injection of all-thiol HMGB1 in mice. In LNCaP cells, azeliragon at 1-10 µM suppressed cell viability and phosphorylation of p38 MAP kinase and NF-κB p65, known as downstream signals of RAGE, but did not upregulate RAGE. Inhibitors of p38 and NF-κB, but not an anti-HMGB1-neutralizing chicken antibody, attenuated the cell viability. Our data suggest that azeliragon suppresses cell viability through suppression of p38 and NF-κB activity downstream of RAGE in LNCaP cells, suggesting its usefulness to treat castration-resistant prostate cancer.